(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Hyperbilirubinemia is one of the clinical phenomena which most often found in newborns. More than 85% of full-term infants who are re-treated within the first week of life are caused by this condition. This study aimed to determine the factors associated with the incidence of hyperbilirubinemia in Arifin Achmad Regional Hospital Pekanbaru City in 2018. This research was a descriptive analytic research with cross sectional approach conducted in August 2019 to April 2020. The population of this study were all sick babies of Arifin Achmad Regional Hospital Pekanbaru City 2018, there were totally 333 infant. Sampling in this study was with a total sampling technique totaling 333 infants with research instruments using the spreadsheet. The data collection was done by using the documentation method. Data analysis using chi square statistical tests with a significance level of 95%.The results showed that the incidence of hyperbilirubinemia in infants at Arifin Achmad Pekanbaru Hospital 2018 was 14.1%. Statistically there is a relationship between asphyxia and the incidence of hyperbilirubinemia in infants (p = 0.048), there is no relationship between Low Birth Weight (p = 0.358) and birth trauma (p = 0.865) with the incidence of hyperbilirubinemia in infants.